A Southwest Pacific Perspective on Long‐Term Global Trends in Pliocene‐Pleistocene Stable Isotope Records. Issue 7 (27th July 2018) - Patterson, M. O.; McKay, R.; Naish, T.; Bostock, H. C.; Dunbar, R.; Ohneiser, C.; Woodard, S. C.; Wilson, G.; Caballero‐Gill, R.
Abstract: Continuous stable isotope records from marine sediment cores spanning the Pliocene have been used to assess the oceans' response to major perturbations in the climate system as the oceans play an integral role in regulating the global distribution of heat and gases. The Early to mid‐Pliocene has previously been characterized as a time of relative warmth followed by Late Pliocene Southern Hemisphere cooling and bipolar glaciation at ~2.7 Ma. Previous studies have predominantly focused on the Atlantic and Equatorial Pacific Oceans. In this study, we extended the deep water benthic foraminifera stable isotope record from Ocean Drilling Program (ODP) Site 1123 in the southwest Pacific, back to the warm Early Pliocene. This is a high‐latitude site at the gateway where the abyssal waters enter the Pacific Ocean and provides information about the connection between the Southern Ocean and the Pacific. We identify a dichotomy between the deep southwest Pacific and South Atlantic δ 13 C records spanning the mid‐Pliocene and suggest that this is most likely the result of variations in the relative contributions of Northern versus Southern Hemisphere deep waters to the different basins. At 3.6 Ma, δ 13 C values start to decrease; this is interpreted to represent alteration in preformed values as a result of increased remineralization of carbon caused by a reduction in deep ocean ventilation in the Southern Ocean. This is likely the consequence of a greater extent and seasonal duration of sea ice in the Southern Ocean from Antarctic Ice Sheet expansion and cooling. Key Points: We present the Early to mid‐Pliocene benthic foraminiferal stable isotope record from the SW Pacific Comparison to global data sets implies deep connection between the Southern Ocean and Pacific Ocean circulation during the Pliocene We identify three major time steps 3.6, 2.7, and 1.5 Ma in which δ 13 C values imply changes in abyssal circulation